Status of Marginalized Children in India: Policy Gaps and Way Forward - Lal, Judith Anne (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
This paper seeks to highlight the situation of marginalized children; especially the socially excluded children from Scheduled Caste (Dalits) and Scheduled Tribes (Adivasis) communities. The attempt is to analyze government policies and schemes in the backdrop of Sustainable Development Goals (SDGs) 16 and United Nations Convention on the Rights of the Child (UNCRC) to promote and protect the rights of these children. Further the paper examines the government programmes thereby proposing policy level changes to promote child centric policies and strategies to protect the rights of dalit and adivasi children.
Keywords: Adivasis; Caste system; Caste based discrimination and violence; Dalits; Discrimination; Equality; Equity; Fundamental rights; Indian constitution; Intersectionality; Patriarchy; Social justice; Sustainable development goals; Scheduled Castes; Scheduled Tribes; Sustainable Development Goals (SDGs) 16; Untouchability; United Nations Convention on the Rights of the Child (UNCRC)